Aphyllophoroid fungi (Basidiomycota) of Tuva Republic, southern Siberia, Russia - Kotiranta, Heikki; Shiryaev, Anton G.; Spirin, Viacheslav (Folia Cryptogamica Estonica, 2016)
The present study reports 227 Aphyllophoroid fungi from Tuva Republic, southern Siberia, Russia. A total of 211 species are new to the republic. The material was collected during August 2014 and includes some surprising species like Haploporus odorus and Polyporus pseudobetulinus, both known as northern taiga species of old-growth forests. Nominates for the new edition of Red Data Book of Tuva are briefly discussed and some microscopical descriptions and illustrations of unidentified or little known species are given.